Is it fair to treat China as a christmas tree to hang everybody's complaints? Putting its own energy saving into perspective - ZhongXiang Zhang (Fondazione Eni Enrico Mattei (FEEM), 2009)
China had been the world's second largest carbon emitter for years. However, recent studies show that China had overtaken the US as the world's largest emitter in 2007. This has put China on the spotlight, just at a time when the world community starts negotiating a post-Kyoto climate regime under the Bali roadmap. China seems to become such a Christmas tree on which everybody can hang his/her complaints. This paper first discusses whether such a critics is fair by examining China's own efforts towards energy saving, the widespread use of renewable energy and participation in clean development mechanism. Next, the paper puts carbon reductions of China's unilateral actions into perspective by examining whether the estimated greenhouse gas emission reduction from meeting the country's national energy saving goal is achieved from China's unilateral actions or mainly with support from the clean development mechanism projects. Then the paper discusses how far developing country commitments can go in an immediate post-2012 climate regime, thus pointing out the direction and focus of future international climate negotiations. Finally, emphasizing that China needs to act as a large and responsible developing country and take due responsibilities and to set a good example to the majority of developing countries, the paper articulates what can be expected from China to illustrate that China can be a good partner in combating global climate change.
Keywords: Q42; Q48; Q53; Q54; Q58; 330; Energy Saving; Renewable Energy; Post-Kyoto Climate Negotiations; Clean Development Mechanism; China; USA